Reversible data hiding in encrypted domain based on fine-grained access control - ZHANG Minqing; PENG Shen; JIANG Chao; DI Fuqiang; DONG Yufeng (Tongxin xuebao)
To improve the embedding rate and security of reversible data hiding algorithms in encrypted images for cloud environments, ciphertext-policy attribute-based encryption and reversible data hiding in encrypted images were organically integrated, and a reversible data hiding algorithm in encrypted images based on fine-grained access control was proposed. Firstly, pixels were classified according to the size of the prediction error value, and different categories of pixels were marked using a parametric binary tree. Secondly, the image encryption key was encrypted based on the ciphertext-policy attribute-based encryption algorithm, and the encrypted key, along with the information to be embedded, was embedded into the encrypted image. It was indicated by experimental results that categorizing the non-embeddable pixeled into self-recording pixels and non-recording pixels reduced the amount of auxiliary information, thus increasing the embedding capacity. Compared with state-of-the-art algorithms, the proposed algorithm achieves an average embedding rate improvement of approximately 0.2 bit/pixel while enabling fine-grained access control of the encrypted images. The algorithm demonstrates high embedding rate, strong security, and perfect reversibility, making it highly practical.